Clinical utility of preoperative evaluation of bronchial arteries by three‐dimensional computed tomographic angiography for esophageal cancer surgery. Issue 6 (13th December 2012) - Wada, T.; Takeuchi, H.; Kawakubo, H.; Nakamura, R.; Oyama, T.; Takahashi, T.; Wada, N.; Saikawa, Y.; Omori, T.; Jinzaki, M.; Kuribayashi, S.; Kitagawa, Y.
Summary An identification of bronchial arteries (BAs) is critical in esophageal cancer surgery to avoid tracheobronchial ischemia and unexpected massive bleeding during surgical procedure particularly in thoracoscopic video‐assisted esophagectomy. We describe the efficacy of three‐dimensional computed tomographic angiography (3D‐CTA) of BAs for preoperative evaluation in esophageal cancer surgery. Sixty‐four patients with esophageal cancer who preoperatively underwent multidetector computed tomography examination were included in this study. We evaluated the number, origin, and intraoperative preservation rate of BAs, and we compared the number of thoracic paratracheal lymph nodes harvested between two groups comprising patients who either underwent preoperative 3D‐CTA of BAs (3D‐CTA group) or did not (non‐3D‐CTA group). The right and left BAs were preoperatively identified in 62 patients (97%) and 55 patients (86%), respectively, using 3D‐CTA. In 34 patients (53%), the right BA originated as a common trunk with the right intercostal artery. In 48 patients (75%), the left BA originated from the descending aorta as a single or double branch. Some anomalies such as the right BA originated from the left subclavian artery were observed. In all patients, either the right or the left BA was preserved. The number of harvested lymph nodes in left side of paratrachea was significantly increased in 3D‐CTA group, than those in non‐3D‐CTA group. 3D‐CTA clearly revealed BA anatomy, contributing to BA preservation and safe and precise lymphadenectomy in esophageal cancer surgery. 3D‐CTA of BAs is useful for preoperative evaluation in esophageal cancer surgery.